Assessing the impact of shallow subsurface pipe drainage on soil salinity and crop yield in arid zone - Yang,Haichang; Chen,Weiye; Chen,Yun; Zhang,Fenghua; Yang,Xiaohu (PeerJ, 2021)
Purpose Soil salinization is one of the key problems of sustainable development of arid agricultural land. Exploring the use of shallow subsurface pipe drainage to improve soil salinization. Methods This study investigates the desalinization effect of shallow subsurface pipe drainage, in combination with drip irrigation under plastic mulch, in an arid region in China. Field data collection was conducted in 2010. Soil salinity at a range of soil depths, water EC and pH of subsurface pipe drainage and crop yield during crop growth stages in salinized farmlands were measured. Results and Conclusion The results show that soil salinity was reduced significantly on mildly (1–3 dS m−1) and moderately (3–6 dS m−1) salinized farmlands. The highest desalinization rate of mildly and moderately salinized soils was 51% and 91% respectively. The desalinization in upper soil layers, to a depth of 60 cm, was more significant than that in lower soil layers. Drainage water salinity was much higher than irrigation water salinity. Crop yield on mildly and moderately salinized land increased about 25% and 50%, respectively. This indicates that the combination of drip irrigation and shallow subsurface pipe drainage on farmlands is potential feasible to desalt farmlands and to improve crop yield. The study has led to a desalinization of 330 ha year−1 in Xinjiang.
Keywords: Soil salinization; Drip irrigation; Plastic mulch; Growth stage; Desalinization